Representasi Asia Tenggara dalam Berita tentang Covid-19 di Media Barat - Morissan Morissan (Jurnal ILMU KOMUNIKASI, 2023)
This study aims to explore how the Western media determine news sources, frames, and news tone for events related to Covid-19 in Southeast Asia. Using the comparative content analysis, the findings show that news is presented in a negative tone while most news is presented frameless (65.8%), while news that uses frames includes a frame of responsibility (14.6%) and human interest (12.2%). Statistic test shows that there is no significant difference between Western media in the use of news sources, framing, and tone of the news. Keywords: representation, Western media, Southeast Asia, news, Covid-19